Detection Method for Escherichia coli Using Real-Time Polymerase Chain Reaction Targeting the yhaV Gene - Nurjayadi, Muktiningsih; Fitriyanti, Anisa; Musie, Royna Rahma; Putri, Gusti Angieta; Azizah, Puan Aqila; Angelina, Helzi; Grace, Grace; Sihombing, Ananda Indah Putri; Setiawan, Agus; Declan, Jefferson Lynford; Putri, Gladys Indira; Juliansyah, Dandy Akbar; Fatimah, Siti; Berkahingrum, Ayu; Kartika, Irma Ratna; Kurniadewi, Fera; Saamia, Vira; Chen, Shyi-Tien; Aboemolak, Bassam; Enshasy, Hesham Ali El (UI Scholars Hub, 2025)
Escherichia coli is a foodborne pathogenic bacterium that can cause diarrhea, while yhaV is a virulence-associated gene linked to the toxin–antitoxin system in E. coli. This study was aimed at evaluating the confirmation, specificity, and sensitivity of a yhaV gene primer using real-time polymerase chain reaction. The yhaV-targeting PCR successfully amplified a DNA fragment with an amplicon length of 207 bp (base pairs) under an annealing temperature optimized to a range of 54 °C to 62 °C via gradient PCR. The PCR using the primer pair produced a consistent Ct (cycle threshold) of 14.14 ± 0.05 and showed a single peak in the melting curve at a Tm (melting temperature) of 83.67 °C ± 0.02. The specificity test indicated that the yhaV primer effectively distinguished E. coli from nontarget bacteria on the basis of differences in Ct and Tm values. The sensitivity analysis showed that the PCR directed toward the primer pair successfully detected E. coli at a minimum concentration of 2.24 pg/µL, with a Ct value of 29.93 and a detection limit of 31.5 × 102 CFU. These results suggest that yhaV-based real-time PCR quickly and accurately identifies E. coli. Primer designs that target yhaV have the potential to be developed as components of a rapid, specific, and sensitive kit for detecting E. coli in food samples.